Analyzing Alkyl Bromide Genotoxic Impurities in Febuxostat Based on Static Headspace Sampling and GC-ECD - Alexandros Kavrentzos; Elli Vastardi; Evangelos Karavas; Paraskevas D. Tzanavaras; Constantinos K. Zacharis (MDPI AG, 2024)
Herein, a sensitive and selective gas chromatography-electron capture detector (GC-ECD) method was developed and validated for the quantification of trace levels of five bromo-containing genotoxic impurities in Febuxostat active pharmaceutical ingredient (API) after headspace sampling (HS). Multivariate experimental designs for the optimization of static headspace parameters were conducted in two stages using fractional factorial design (FFD) and central composite design (CCD). The optimum headspace conditions were 5 min of extraction time and a 120 °C extraction temperature. Baseline separation on the analytes against halogenated solvents was carried out using an Agilent DB-624 (30 m × 0.32 mm I.D., 1.8 μm film thickness) stationary phase under isothermal conditions. The method was validated according to ICH guidelines in terms of specificity, linearity, the limits of detection and quantification, precision and accuracy. The linearity was assessed in the range of 5-150% with respect to the specification limit. The achieved LOD and LOQ values ranged between 0.003 and 0.009 and 0.01 and 0.03 μg mL−1, respectively. The accuracy of the method (expressed as relative recovery) was in the range of 81.5-118.2%, while the precision (repeatability, inter-day) was less than 9.9% in all cases. The validated analytical protocol has been successfully applied to the determination of the impurities in various Febuxostat API batch samples.